Analysis of the Role of Input Markets and Output Markets in Increasing Productivity, Competitiveness, and Economic Welfare: Perspectives of Conventional Economics and Islamic Economics. - Pephitasya Juliana; Siradjuddin; Abdul Wahab (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The input market and the output market are two fundamental elements in the economic system that play an important role in determining the level of productivity, competitiveness, and economic welfare. The input market provides various factors of production, such as labor, capital, land, and entrepreneurship needed in the production process, while the output market is a means of distributing goods and services to consumers. In the conventional economy, market efficiency is the main factor in optimizing the allocation of resources to achieve economic growth and community welfare. Meanwhile, Islamic economics not only emphasizes efficiency, but also prioritizes the principles of justice, balance, benefit, and the achievement of falah as the ultimate goal of economic activity. This research aims to analyze the role of input markets and output markets in increasing productivity, competitiveness, and economic welfare through the perspective of conventional economics and Islamic economics. The method used is library research with a descriptive-comparative approach through the analysis of various literatures, scientific journals, books, and relevant research results. The results of the study show that the input market and the output market have a significant contribution in encouraging productivity through optimizing the use of production factors and increasing the efficiency of production distribution. In the perspective of conventional economics, productivity and competitiveness are influenced by price mechanisms, market competition, and resource allocation efficiency. As for the perspective of Islamic economics, productivity and competitiveness are not only measured in terms of economic profits, but also by the extent to which market activities are able to create distribution justice, avoid exploitative practices, and provide benefits to society at large. Therefore, the integration of conventional economic efficiency values with sharia principles can be an alternative in realizing a productive, competitive, and welfare-oriented market system.